The Philosophical Arguments in the Dispute over Artificial Reproduction in Italy in the Years 2004–2014 - Kobyliński, Andrzej (Studia Ecologiae et Bioethicae, 2020)
In Italy for the last decade, a very interesting public debate has been conducted about artificial reproduction. An important step in this discussion was the adoption in 2004 of a special law regulating the use of the in vitro method. In 2014 the Constitutional Court cancelled the prohibition, existing in this document, of the methods of heterological artificial reproduction. A very important part of the debate in Italy are different kinds of philosophical arguments. The most interesting or very representative voices in this discussion include statements of Oriana Fallaci, Vittorio Possenti, and Gianni Vattimo.